Memorial Projeto Rondon: um espaço de pesquisa, preservação e valorização da história do Projeto Rondon na UFSM - Spiazzi, Daiane Tonato (2011)
In the same year the Federal University of Santa Maria (UFSM) completes 50 years of creation and 42 years of participation in the Rondon Project, it was considered relevant to create a Rondon Project Memorial, being this a Museum space, focused in research, preservation and valorization of the History of the Rondon Project in UFSM. The Rondon Project Memorial was created through one Project linked to the ExtensionDepartment, following the rules of the Museum Statute, according the Law 11.904, from January, 14th, 2009. The Memorial has the goal to acquire, research, teach, catalogue, put in place and show, systemically, documents, icon materials, videos and objects concerning to the Rondon Project trajectory in the National territory, as well the activities of extension developed by the UFSM, in the Rondon Project since 1968. And through this work, the goal is to valorize the History of the University, that during its long trajectory was focused on teaching, researching and extension, priming for the regional developing and community attendance. With this, and with the boldness of its academics, professorsand directors, having for main character the Professor Doctor José Mariano da Rocha Filho, who dreamed, planned and created the first Federal University outside one capital, the UFSM has become a reference center in all Brazil. Doctor Mariano, through his work and vanguard actions, inspired in United States universities, made UFSM a multiuniversity, as so, a multiple campi University, extending its dominium and influence to almost 45% of the Rio Grande do Sul territory and, also, beyond it, installingan Advanced Campus at more than 5 thousand kilometers from its main house. The installation in 1969, of the Advanced Campus in Boa Vista, Roraima, Brazil, happened thanks to the Rondon Project, which maintained, in its first phase, from 1968 to 1989, the Project of Advanced Campus, besides National, Regional, Special and Interiorization Operations. Having the goal of social interaction, through operations in the school vacations period, which permited to the academic from Brazilian universities practice their knowledge and, at the same time, to know different realities, and through their work contribute to the development of needy communities around the country. The Rondon Project, that was extinct with the political opening, returned their activities, being coordinated by the Defense Ministry, with the support of the Education Ministry, in the year 2005, having also the support of the President LuizInácio Lula da Silva.The UFSM already made part in the first National Operation, carried out in January, 2005, in Tabatinga, AM, having like Coordinator of the Project in UFSM, the Professor UbiratanTupinambá da Costa, who, during six years, from 1977 to 1982, has been Director of the Advanced Campus in Boa Vista, Roraima, Brazil. Him, like the other who made part of the Rondon Project Operations has a rich memory and large archives about the Project, meanwhile, they are inaccessible or forgotten.And it is because of that, it was considered necessary to create a Memorial to save this registers so precious for the Rondon Project History and the UFSM.